ANALISIS RANTAI PASOK SAYURAN HIDROPONIK DI KOTA BANDAR LAMPUNG (Studi Kasus pada Merek Sahabat Hidroponik dan Sayuran Kita) - Nike Margie Utami; Rabiatul Adawiyah; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2023)
The horticultural subsector is still a special concern in the context of developing agribusiness with the development of hydroponic vegetable producers in Bandar Lampung City.  However, the supply process experiences constraints related to product inventory, product quality, and unpredictable demand.  Supply chain is an approach to solve problems that occur. Based on this description, this study aims to analyze product flow, money flow, information flow, and supply chain conditions of Sahabat Hidroponik and Sayuran Kita.  The research was carried out in April - July 2022 using the case study method.  Respondents in this study were 18 people consisting of producers (producer farmer partners, Sahabat Hidroponik and Sayuran Kita), retail (supermarkets) and consumers.  The data analysis used was descriptive qualitative with the Food Supply Chain Network (FSCN) model.  The flow of products, the flow of money and the flow of information that occurs in hydroponic vegetable producers Sahabat Hidroponik and Sayuran Kita are already doing well between producer farmer partners, producers, retailers, and consumers.  However, the flow of money to some perpetrators has not been effective.  The conditions of the hydroponic vegetable supply chain of Sahabat Hidroponik and Sayuran Kita have shown in quite good conditions.  However, the contractual agreements and transaction systems on some actors have not gone well. Key word : FSCN, hydroponic vagetables, supply chain, supply chain flow